2022
DOI: 10.1111/jocd.14963
|View full text |Cite
|
Sign up to set email alerts
|

Combination of platelet‐rich plasma and platelet gel in treatment of resistance androgenic alopecia: A case series study

Abstract: Background Androgenic alopecia is a common genetic disorder that characterized by progressive hair follicles and hair atrophy. Despite all available therapeutic techniques, there is low patient satisfaction rate. It seems finding new treatment options for androgenic alopecia is necessary. In the past decade, platelet‐rich plasma (PRP), an autologous collection of concentrated platelets with hemostatic and tissue repairing effects, has received developing attention for androgenetic alopecia treatment as a valua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…An insightful case study that demonstrates the efficacy of herbal treatments in managing alopecia is presented by Lotfi et al (2022). This study focused on the combination of platelet-rich plasma (PRP) and platelet gel in treating resistant androgenic alopecia, a common form of hair loss.…”
Section: Case Studymentioning
confidence: 99%
“…An insightful case study that demonstrates the efficacy of herbal treatments in managing alopecia is presented by Lotfi et al (2022). This study focused on the combination of platelet-rich plasma (PRP) and platelet gel in treating resistant androgenic alopecia, a common form of hair loss.…”
Section: Case Studymentioning
confidence: 99%
“…Many studies reported a reduction in hair loss 3 to 12 months following treatment, confirmed by a negative pull test in 70 to 100% of patients. 61,62 A recent meta-analysis revealed that 3 monthly PRP injections are effective for AGA treatment. PRP can increase total hair density by 25.61 hair/cm 2 (95% confidence interval [CI]: 4.45 to 46.77; p ¼ 0.02) compared to placebo.…”
Section: Nonsurgical Nonmedical Treatmentmentioning
confidence: 99%